Pengaruh Struktur Kepemilikan Institusional, Likuiditas dan Leverage Terhadap Financial Distress pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2021 - Michael; Angella Simon; Putra Sanjaya Simanjuntak; Dita Eka Pratiwi Sirait; Ribka Sari Butar-butar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze the impact of institutional ownership, liquidity, and leverage on financial distress. The data for this study were obtained from the Annual Financial Reports published by Telecommunication Companies listed on the Indonesia Stock Exchange for the period 2018–2021. A total of 72 telecommunications companies listed on the Indonesia Stock Exchange between 2018 and 2021 were sampled using this technique. Applying analytical methods, such as logistic regression approach in statistical testing, the research findings indicate that the combined effect of leverage, liquidity, and institutional ownership on financial distress is 42.8%. Institutional ownership influences Financial Distress to some extent. Financial Distress is not affected by the Liquidity variable. There is no impact of leverage on financial distress. Institutional ownership, liquidity, and leverage variables can explain 42.8% of the Financial Distress variable, while other variables not included in the study explain the remaining 57.2%, according to the coefficient of determination (R2) value of the study, which is 0.428.